IgA Vasculitis Nephritis: A Case Series and Comparison of Treatment Guidelines - Al Harash, Abdalhamid (Case Rep Rheumatol, 2020)
Immunoglobulin A (IgA) vasculitis nephritis (IgAVN) and IgA nephropathy (IgAN) share many pathological parallels and are viewed as related diseases by many groups. Current treatment guidelines remain vague, controversial, and without consensus, especially regarding the role of immunosuppressive medications. We present five cases of IgAVN encountered at our tertiary care center between 2016 and 2020, which were treated with different immunosuppression regimens. Infection was the leading cause of death in this series. These cases provide evidence that IgAVN should be distinguished from IgAN on a spectrum of IgA-associated glomerulonephritis. The outcomes presented herein suggest that the morbidity and systematic involvement IgAVN is greater than previously believed and that these substantial risks should be reflected in contemporary treatment guidelines.